Handheld Secured Electronic Doorstep Banking System that allows Cash Withdrawal and Deposit Facility for Remote and Rural Areas - G. Kannan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The bank's similar massive customer base isn't inside the urban level notwithstanding, inside the repeatedly pretermitted rustic territories. Light errands like getting without end to the ATM and withdrawing trade cause people out towns lose their working hours and, thus, miss a major live of their monetary profit moreover. In this paper a secured handheld doorstep managing an account industry alluded to as Micro-bank machine is proposed to concede administration to the buyers in provincial ranges and remote places, for example, towns. The arranging may likewise be worked inside and on the most distant side of the consistent managing an account hours. The primary point of the handheld machine is to control managing an account administration like cash withdrawals and cash store while not the individual always pointing to a bank even in remote territories wherever even a GSM cell affiliation isn't conceivable.